How to: design for context. Getting clear on geography, power, and governance - Larson, A.M.; Sarmiento Barletti, J.P. (CIFOR-ICRAF, 2023)
So you’ve mapped existing and past experiences with MSPs in your landscape, and decided that you want to implement one. Now it’s time to home in on context – the resources, actors, governance arrangements, power structures and relationships, and conflicts that exist within, or affect, the landscape in question.